Association Between Statin Use and Prognosis of Breast Cancer: A Meta-Analysis of Cohort Studies - Hui Lv; Ding Shi; Min Fei; Yu Chen; Fei Xie; Zhuoyan Wang; Ying Wang; Peiying Hu (Frontiers in Oncology, 2020)
Background: Statin, a lipid-lowering drug, has been suggested to confer anticancer efficacy. However, previous studies evaluating the association between statin use and prognosis in breast cancer showed inconsistent results. A meta-analysis was performed to evaluate the association between statin use and clinical outcome in women with breast cancer.Methods: Cohort studies comparing recurrence or disease-specific mortality in women with breast cancer with and without using of statins were identified by search of PubMed, Embase, and Cochrane's Library databases. A random-effect model, incorporating the inter-study heterogeneity, was used to combine the results. Subgroup analyses were performed to evaluate the influences of study characteristics on the outcomesResults: Seventeen cohort studies with 168,700 women with breast cancer were included. Pooled results showed that statin use was significantly associated with a lower risk of breast cancer recurrence (adjusted hazard ratio [HR] = 0.72, p < 0.001) and breast cancer mortality (HR = 0.80, p < 0.001). Subgroup analysis showed that timing of statin use, statin type, study design, sample size, or quality score did not significantly affect the outcomes. However, statin use was associated with more remarkably reduced breast cancer recurrence in studies with mean follow-up duration ≤ 5 years (HR = 0.55, p < 0.001) than that in studies of >5 years (HR = 0.83, p = 0.01).Conclusions: Statin use is associated with reduced recurrence and disease-specific mortality in women with breast cancer. These results should be validated in randomized controlled trials.